THE INFLUENCE OF SPIRITUAL SKILL, DISCIPLINE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. TOYS GAMES INDONESIA - AGUSTINI AGUSTINI; NURYANTI NURYANTI; RIZAL BAKTI; KRISNA SUDJANA; MEI ISWANDI; JHONSON SITANGGANG (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The kind of research used is a quantitative research using the research method of data collection using a questionnaire. The data analysis model used was a linear regression analysis with sample 32. The study suggests 61,0% of an employee’s performance factors can be affected by spiritual skill, discipline, and work motivation. In comparison, the rest, 39,0%, are affected by other unexamined factors in the study. In contrast, the results of the F show that simultaneous spiritual skill, discipline, and work motivation simultaneously affect positive and significant effects on employees’ performance. The results of the t-test show that the spiritual skill variable and work motivation are both positive and significant. In contrast, the discipline variable has no positive or significant effect on employee performance at PT. Toys Games Indonesia.